MEASUREMENT OF EFFICIENCY AND EFFECTIVENESS OF ZAKAT MANAGEMENT IN THE NATIONAL BOARD OF ZAKAT (BAZNAS) WEST JAVA - Kartini Kartini; Efri Syamsul Bahri; Ahmad Baehaqi (UIN Mataram, 2021)
This study aims to analyze the efficiency and effectiveness of the management of zakat and infaq/alms at the National Board of Zakat (Baznas) West Java for 2015-2019. Measuring efficiency uses a data envelopment analysis (DEA) approach. Measurement of effectiveness uses an allocation-to-collection ratio (ACR) approach. Data obtained from Baznas West Java comes from financial reports for the 2015-2019 period. The results showed the value of the efficiency of zakat management in the efficient category. The efficiency value in the 2016-2019 range reaches 100% each year. Then, the value of zakat distribution's effectiveness for the 2015-2019 period is in the highly effective category. The value of the effectiveness of infaq/alms distribution for the 2015-2019 period is in the effective category. The effectiveness of zakat distribution every year is bellows expectation (2015), effective (2016), highly effective (2017), highly effective (2018), and highly effective (2019). The effectiveness of infaq/alms distribution every year is effective (2015), fairly effective (2016), effective (2017), bellows expectation (2018), and highly effective (2019). The implication of this research is to increase public trust and confidence that the zakat they pay has and will be used efficiently and effectively by zakat management organizations. Then, suppose it is associated with Sharia Enterprise Theory. In that case, this study's implications refer to and strengthen the exogenous variables, namely accountability and transparency of financial reporting, which are the motivating factors for muzakki to pay their zakat to the Zakat Management Organization.